Do Temporal Regularities during Maintenance Benefit Short-term Memory in the Elderly? Inhibition Capacities Matter. Issue 5 (19th October 2020) - Fanuel, Lison; Portrat, Sophie; Dalla Bella, Simone; Tillmann, Barbara; Plancher, Gaën
ABSTRACT: Background/Study context: Recent research has shown a benefit of temporally regular structure presented during the maintenance period in short-term memory for young adults. Because maintenance is impaired in aging, we investigated whether older adults can also benefit from the temporal regularities for maintenance and how their cognitive capacities might affect this potential benefit. Methods: Healthy older adults (range: 63–90 years old) had to memorize visually presented letters and maintain them in short-term memory for 6 s until recall. The six-second retention interval was either filled with an isochronous rhythmic sound sequence that provided a temporally regular structure or silent. Results: The effect of the isochronous rhythm on recall performance was modulated by inhibition capacities of older adults: as compared to silence, improved recall performance thanks to the rhythm emerged with increased inhibitory capacity of the participants. Conclusion: Even though maintenance of older adults benefits less from the presence of temporal regularities than does the maintenance of younger ones, our findings provide evidence for improved maintenance in short-term memory for older adults in the presence of a temporally regular structure, probably due to enhanced attentional refreshing. It further provides perspectives for training and rehabilitation of age-related working memory deficits.